On the proposed martensitic-like structural transformation in V, Nb, and Ta - Cordero, F. (Физика низких температур, 2018)
The transition metals Nb, Ta and V have been known to be cubic at all temperatures, until recently the existence of a martensitic transformation has been reported, based on anomalies in the thermal expansion at low temperatures. Such a structural transformation would have passed unnoticed, because it would be hindered by small amounts of impurities. This finding is discussed in the light of anelastic measurements on Nb samples whose purities are comparable to those presenting the dilatometric anomalies. It results that the effects of the alleged transformation on the anelastic spectra would be at least three orders of magnitude smaller than in typical martensitic transformations. A possible alternative explanation for the observed anomalies is proposed in terms of precipitation of unnoticed residual H.